2024
DOI: 10.3389/fimmu.2023.1284609
|View full text |Cite
|
Sign up to set email alerts
|

Osteo-immunological impact of radon spa treatment: due to radon or spa alone? Results from the prospective, thermal bath placebo-controlled RAD-ON02 trial

Denise Eckert,
Megi Evic,
Jasmin Schang
et al.

Abstract: Musculoskeletal disorders (MSDs) are associated with pain and lead to reduced mobility and quality of life for patients. Radon therapy is used as alternative or complementary to pharmaceutical treatments. According to previous reports, radon spa leads to analgesic and anti-inflammatory effects, but the cellular and molecular mechanisms are widely unknown. A previous study (RAD-ON01) revealed, that bone erosion markers like collagen fragments (C-terminal telopeptide, CTX) are reduced after radon spa treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(98 reference statements)
1
0
0
Order By: Relevance
“…However, one can notice that the increase in regulatory T cell counts occurs earlier after radon baths than after sole warm water applications and a higher level of significance is reached for the modulations after radon spa (see Figure 4B). This finding is in line with the observations of Eckert et al, who analyzed the regulatory T cell to Th17 ratio in a subgroup of patients of the RAD-ON02 study via intracellular FACS staining, and found a significant increase of regulatory T cells only after radon spa (43). Some studies state that spa applications in general impact on the immune system, for example by the modulation of cytokines, adipokines and other serum proteins, which is in line with the immune modulations that have been observed after radon and warm water applications.…”
Section: Discussionsupporting
confidence: 92%
“…However, one can notice that the increase in regulatory T cell counts occurs earlier after radon baths than after sole warm water applications and a higher level of significance is reached for the modulations after radon spa (see Figure 4B). This finding is in line with the observations of Eckert et al, who analyzed the regulatory T cell to Th17 ratio in a subgroup of patients of the RAD-ON02 study via intracellular FACS staining, and found a significant increase of regulatory T cells only after radon spa (43). Some studies state that spa applications in general impact on the immune system, for example by the modulation of cytokines, adipokines and other serum proteins, which is in line with the immune modulations that have been observed after radon and warm water applications.…”
Section: Discussionsupporting
confidence: 92%